Technology and Place : Sustainable Architecture and the Blueprint Farm - Moore, Steven A., 1945- (Book collections on Project MUSE., 2001)
Developing "sustainable" architectural and agricultural technologies was the intent behind Blueprint Farm. In this book, Steven Moore demonstrates how the various stakeholders' competing definitions of "sustainability," "technology," and "place" ultimately doomed Blueprint Farm.